Chlorine-resistant polyethylene pipe and preparation method thereof
By coating the tuner graphene layer in the inner wall of polyethylene pipes, the problem of accelerating degradation of polyethylene pipes in chloride ion environments has been solved, and the effect of significantly improved chlorine resistance and extending service life.
Patent Information
- Application Number
- CN202310927251.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2023-07-26
- Publication Date
- 2025-01-28
AI Technical Summary
When polyethylene pipes encounter disinfectants such as sodium hypochlorite, they will release more chloride ions, causing the accelerated degradation of polyethylene pipes and significantly reduced their service life. In the prior art, antioxidants or acid removers are used to improve chlorine resistance, but the effect is not good.
Pailor the modified graphene layer in the inner wall of polyethylene pipes. Through graphene and polyethylene glycol, the degraded graphene is evenly dispersed in the polyethylene alcohol alcohol to form a barrier layer to improve the chlorine resistance of the pipe system Essence
Through the resistance of the modified graphene layer, the corrosion resistance of polyethylene pipes to chloride ions is significantly improved, the service life is prolonged, and the process is simple and cost -effective.
Smart Images

Figure CN119373950A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the field of plastic pipes, and in particular, relates to a chlorine-resistant polyethylene pipe with a graphene coating, and a preparation method of the chlorine-resistant polyethylene pipe. Background Art
[0002] Plastic pipes have the characteristics of simple molding, low specific gravity, and resistance to acid and alkali corrosion. They are gradually replacing metal pipes and are widely used. The processing and molding conditions of polyethylene materials are simple, making it the most important base material for plastic pipes. However, in actual use, in addition to acid and alkali corrosion, plastic pipes will also encounter corrosion from other substances in their use environment. For example, sodium hypochlorite, which is often used as a disinfectant, will release more chloride ions. Chloride ions will also have a significant impact on plastic pipes, especially polyethylene pipes, causing polyethylene pipes to accelerate degradation and significantly reduce the service life of polyethylene pipes. In order to overcome this effect, the prior art usually improves the chlorine resistance of the material by adding antioxidants or acid scavengers to the polyethylene resin matrix, but antioxidants will be lost in large quantities during the processing process and the additives are easier to migrate, resulting in poor actual chlorine resistance. Therefore, methods for improving the chlorine resistance of polyethylene pipes are very important and have a very broad market application space. Summary of the invention
[0003] The object of the present invention is to provide a chlorine-resistant polyethylene pipe and a preparation method thereof. The inner wall of the polyethylene pipe of the present invention has a layer of modified graphene coating, and the modified graphene material in the coating undergoes a grafting reaction with polyvinyl alcohol (PVA) during the preparation process, thereby being uniformly dispersed in the PVA matrix. After the modified graphene material is coated on the inner wall of the polyethylene pipe as a barrier layer, the corrosion resistance of the polyethylene pipe to chloride ions is significantly improved.
[0004] To achieve the above-mentioned purpose, the first aspect of the present invention provides a chlorine-resistant polyethylene pipe, which comprises a polyethylene resin layer as an outer layer and a modified graphene coating as an inner layer, wherein the modified graphene coating is a polyvinyl alcohol edge-grafted modified graphene coating, and at least part of the polyvinyl alcohol forms a cross-linked polyvinyl alcohol; based on the total mass of the modified graphene coating as 100%, the mass content of polyvinyl alcohol in the modified graphene coating is 3-30%, preferably 5-25%, and the mass content of graphene is 70-97%, preferably 75-95%.
[0005] The second aspect of the present invention provides a method for preparing the above-mentioned chlorine-resistant polyethylene pipe, comprising the following steps:
[0006] (1) mixing polyvinyl alcohol, water and graphite uniformly, grinding them in a grinding wheel kettle, standing them to remove the precipitate after grinding, and obtaining an aqueous dispersion of polyvinyl alcohol edge-grafted modified graphene;
[0007] (2) adding a cross-linking agent and an optional catalyst to the aqueous dispersion to obtain a modified graphene dispersion;
[0008] (3) coating the modified graphene dispersion on the inner wall of a polyethylene pipe and drying the pipe to obtain the chlorine-resistant polyethylene pipe.
[0009] The third aspect of the present invention provides another method for preparing the above-mentioned chlorine-resistant polyethylene pipe, comprising the following steps:
[0010] (1) mixing polyvinyl alcohol, water and graphite uniformly, grinding them in a grinding wheel kettle, standing them to remove the precipitate after grinding, and obtaining an aqueous dispersion of polyvinyl alcohol edge-grafted modified graphene;
[0011] (2) coating the aqueous dispersion of the polyvinyl alcohol edge-grafted modified graphene on the inner wall of a polyethylene pipe, and performing physical crosslinking or radiation crosslinking and drying to obtain the chlorine-resistant polyethylene pipe.
[0012] Compared with other technical solutions, the present invention uses a simple and cost-controlled graphene preparation technology to develop modified graphene materials based on low-cost and easily available graphite materials, and coats the modified graphene materials on the inner wall of polyethylene pipes to achieve excellent chlorine resistance of polyethylene pipes. The use of antacids and other methods in other solutions cannot play a similar isolation role as the modified graphene material of the present invention.
[0013] Other features and advantages of the present invention will be described in detail in the following detailed description. BRIEF DESCRIPTION OF THE DRAWINGS
[0014] Exemplary embodiments of the present invention will be described in more detail with reference to the accompanying drawings.
[0015] Figure 1 This is an infrared absorption spectrum of PVA edge-grafted graphene prepared in Example 1, where the upper curve represents flake graphite, the middle curve represents PVA, and the lower curve represents PVA-grafted graphene;
[0016] Figure 2 This is a scanning electron microscope photo of the PVA edge-grafted graphene prepared in Example 1;
[0017] Figure 3 This is a transmission electron microscope photograph of the PVA edge-grafted graphene prepared in Example 1.
[0018] Figure 4 This is a thermogravimetric analysis graph of PVA edge-grafted graphene prepared in Example 1. The upper curve represents flake graphite, the middle curve represents PVA grafted graphene, and the lower curve represents PVA. DETAILED DESCRIPTION
[0019] The specific embodiments of the present invention are described in detail below. It should be understood that the specific embodiments described herein are only used to illustrate and explain the present invention, and are not used to limit the present invention.
[0020] The first aspect of the present invention provides a chlorine-resistant polyethylene pipe, which includes a polyethylene resin layer as an outer layer and a modified graphene coating as an inner layer, wherein the modified graphene coating is a polyvinyl alcohol edge-grafted modified graphene coating, and at least part of the polyvinyl alcohol forms a cross-linked polyvinyl alcohol; based on the total mass of the modified graphene coating as 100%, the mass content of polyvinyl alcohol in the modified graphene coating is 3-30%, preferably 5-25%, and the mass content of graphene is 70-97%, preferably 75-95%.
[0021] In view of the problems in the prior art, the inventor intends to use the lamellar structure of graphene to block corrosive ions and other substances, so as to improve the chlorine resistance of polyethylene pipes. However, conventional graphene materials are difficult to disperse evenly in the polymer matrix and thus cannot achieve an effective barrier effect. Only graphene materials with functional group modification, such as graphene oxide, can improve this problem. However, a large amount of strong acid and strong oxidant, such as concentrated sulfuric acid, fuming nitric acid, potassium permanganate, perchloric acid, etc., are used in the preparation method of graphene oxide, causing serious waste liquid pollution and being unsuitable for large-scale use. The present invention peels off the graphite by physical method, and in the process of peeling off, PVA and the peeled graphene material undergo grafting reaction, thereby enhancing the interaction between the PVA matrix and graphene, and promoting the uniform dispersion of the graphene material in the matrix. The composite material of PVA and graphene prepared by the present invention is used as the inner coating of the pipe, which can play a good barrier effect and greatly improve the chlorine resistance of the polyethylene pipe. And the preparation process is simple, easy to implement, and has strong market competitiveness.
[0022] In the present invention, the mass content of polyvinyl alcohol in the modified graphene coating is measured by thermogravimetric analysis: under the conditions of a sample nitrogen flow rate of 20.0 ml / min and a balance nitrogen flow rate of 40.0 ml / min, the mass loss of the PVA edge-grafted modified graphene sample is measured from 50.00°C to 800.00°C at a heating rate of 20.00°C / min, that is, the mass content of PVA grafted to the graphene.
[0023] The oxidation induction period of the chlorine-resistant polyethylene pipe of the present invention after being soaked in a chlorine-containing aqueous solution is greater than 25 minutes; the concentration of the chlorine-containing aqueous solution is 10-100 mg / L, and the soaking time is more than 3 weeks. In a specific example, the oxidation induction period of the polyethylene material of the chlorine-resistant polyethylene pipe after being soaked in a chlorine-containing aqueous solution (chlorine concentration is 15 mg / L) for 4 weeks remains above 25 minutes, and some can reach more than 30 minutes.
[0024] The present invention has no particular limitation on the polyethylene pipe, and the polyethylene material used can be any polyethylene material and a composition of polyethylene materials, and the composition can contain various additives for improving the oxidation resistance and physical properties of the polyethylene pipe, including but not limited to antioxidants, acid scavengers, organic or inorganic fillers, etc. The pipe forming method can also be any conventional method.
[0025] The thickness of the modified graphene coating can be determined according to the use requirements of the chlorine-resistant polyethylene pipe. Generally, a modified graphene coating of 0.1-2 mm can have excellent chlorine resistance.
[0026] In the modified graphene coating of the present invention, at least part of the polyvinyl alcohol exists in the form of a gel of cross-linked polyvinyl alcohol. Specifically, based on the total weight of the polyvinyl alcohol in the modified graphene coating as 100%, the gel content of the modified graphene coating is 60-100%, preferably 65-95%.
[0027] The crosslinking of the modified graphene material is the crosslinking of PVA in the composition, and the method used is the physical and / or chemical method of PVA crosslinking in the prior art. The chemical crosslinking method is to form a stable crosslinking agent structure inside the PVA by reacting the hydroxyl groups on the PVA side chain with the functional groups of other compounds, which has better water resistance and stability than the physical method. According to a specific embodiment of the present invention, the modified graphene coating can be formed by drying the modified graphene dispersion coated on the inner wall of the polyethylene resin layer; the modified graphene dispersion includes a water dispersion of polyvinyl alcohol edge-grafted modified graphene and a crosslinking agent. The crosslinking agent that can be added in the chemical method includes but is not limited to at least one of aldehydes, acids, propylene oxide, and heavy metal salts, preferably at least one of glutaraldehyde, boric acid, and oxalic acid. When using a chemical crosslinking agent, the crosslinking agent is 10%-50% of the total mass of PVA. Too little crosslinking agent will result in too few crosslinking points of PVA, which is easy to fall off after encountering water; too high a crosslinking agent affects the cost, so it is more preferably 10%-35%. When chemical cross-linking agents are used, a small amount of acid or base is usually added to the cross-linking system in addition to the acid to catalyze the reaction.
[0028] Among them, the aqueous dispersion of the polyvinyl alcohol edge-grafted modified graphene can be obtained by peeling off the graphite material through a grinding disc. The present invention realizes the process of preparing graphene materials by peeling off the graphite material with the assistance of the PVA aqueous solution through the grinding disc peeling process. The controllable preparation of the graphene sheet structure is achieved by the viscosity increase of the system by the PVA aqueous solution and the shearing effect of the grinding disc, and the grafting reaction of graphene and PVA molecular chains is achieved under the action of shear force, so that the PVA molecular chains are connected to the graphene sheet structure, helping the graphene material to be evenly dispersed in the PVA. After this PVA / graphene aqueous solution is evenly coated along the polyethylene pipe in multiple directions, a barrier layer is formed on the inner wall of the polyethylene pipe, which can improve the chlorine resistance of the polyethylene pipe. The stripping rate of this method is 20-50%, preferably 25-40%.
[0029] Specifically, the aqueous dispersion of polyvinyl alcohol edge-grafted modified graphene is prepared by a preparation method comprising the following steps:
[0030] The polyvinyl alcohol, water and graphite are uniformly mixed and ground in a grinding wheel kettle. After the grinding, the mixture is allowed to stand and the precipitate is removed to obtain the aqueous dispersion of the polyvinyl alcohol edge-grafted modified graphene.
[0031] According to a preferred embodiment of the present invention, the grinding wheel kettle is composed of a grinding wheel and a circulation part. The grinding wheel part includes a moving grinding wheel, a fixed grinding wheel and a rotating device, and the circulation part includes a circulation pump, a slurry storage tank and a stirring device. The grinding wheel material can be selected from metal, ceramic, glass, plastic, etc., preferably metal.
[0032] During the disc peeling process, the moving disc / stationary disc transfers the shear force to the graphite flakes between the discs through the aqueous solution of PVA. Under the action of shear stress, the graphite flakes are first oriented along the rotation direction of the disc, and then slowly peeled into thinner graphite flakes, and finally peeled into graphene. During the peeling process, many new edges are generated, and the carbon atoms at the new edges are more active, reacting with PVA in the aqueous solution to generate PVA edge-grafted graphene. The method used in the present invention significantly reduces the damage to the graphite lattice. The viscosity-increasing effect of PVA on the dispersed system and the shear force between the fixed disc and the moving disc more effectively act on the graphite flakes in the slurry, realizing the peeling preparation of graphene. During the peeling process, PVA is grafted to the edge of graphene, so that the prepared graphene is stably dispersed in water.
[0033] The grinding of the present invention can be carried out in a closed or open system. The preparation process can be cyclic grinding at room temperature and normal pressure, and there is no specific requirement for the atmosphere of the system.
[0034] The grinding conditions selected in the present invention may include: a rotation speed of 10-300 rpm, preferably 50-200 rpm; a cycle stripping time of 5-200 hours, preferably 10-150 hours, and more preferably 30-120 hours.
[0035] The PVA in the system of the present invention has two functions: (1) increasing the viscosity of the dispersion system to improve the peeling effect of the grinding disc on the graphite sheet, and (2) grafting to the graphene to make the graphene stably dispersed in the aqueous solution.
[0036] The aqueous dispersion of PVA edge-grafted graphene in the present invention is prepared by mechanically exfoliating graphite with a grinding disc. The graphite that can be used can be natural graphite and / or artificial graphite. The natural graphite can be selected from one or more of flake graphite and block graphite. The artificial graphite can be selected from one or more of thermal cracking graphite and highly oriented thermal cracking graphite. The graphite is preferably flake graphite. The particle size of the graphite can be 5-8000 mesh, preferably 35-3000 mesh, further preferably 50-1600 mesh, and more preferably 50-300 mesh.
[0037] The PVA used in the preparation of the modified graphene material of the present invention can be any PVA and its derivatives, without restrictions on molecular weight, alcoholysis degree, comonomers, etc. The PVA aqueous solution plays a role in increasing the viscosity of the system during the preparation of the graphene composition, and can undergo a grafting reaction with graphene, so the concentration cannot be too low. Too low a concentration will lead to a decrease in the efficiency of stripping and grafting, and too high a concentration will lead to excessive viscosity of the system, thereby consuming more energy. According to a preferred embodiment of the present invention, PVA and water are first mixed, and then graphite is added. Based on the total mass of PVA and water, the mass fraction of the PVA is controlled to be 2-40%, preferably 3-30%, and more preferably 5-20%.
[0038] In the preparation process of the graphene composition, in order to more effectively peel the graphite material, the feeding ratio between the graphite material and PVA is 1:3 to 3:1. The graphite material may not be completely peeled off during the peeling of the grinding disc, so the weight ratio of the graphite material to PVA is different from the weight ratio of graphene in the graphene composition.
[0039] The average size of graphene flakes in the modified graphene material is related to the grinding disc structure, processing time, graphite type and size. If the graphene size is too small, the barrier effect is not good, and if it is too large, it is easy to agglomerate. The thickness of graphene can be used as a reflection of the degree of graphite exfoliation. The smaller the thickness, the better the exfoliation effect, and more graphene edge-grafted PVA will be produced. However, it usually takes a long time to exfoliate when the thickness becomes smaller, which not only affects the efficiency of the entire process, but also affects the size of graphene. Therefore, in order to obtain better barrier properties, the average sheet diameter of the polyvinyl alcohol edge-grafted modified graphene in the polyvinyl alcohol edge-grafted modified graphene coating is 1-5μm.
[0040] In addition to the aforementioned chemical crosslinking method, the crosslinking of PVA can also be carried out by radiation crosslinking. In this case, the modified graphene coating can be formed by physically crosslinking or radiation crosslinking and drying the aqueous dispersion of polyvinyl alcohol edge-grafted modified graphene coated on the inner wall of the polyethylene resin layer. The physical crosslinking method includes repeated freezing, freeze-dehydration, etc. The radiation crosslinking can use at least one of gamma rays, electron beams, X-rays and ultraviolet light. Compared with crosslinking by adding a crosslinking agent, radiation crosslinking has better uniformity.
[0041] According to the above two different types of cross-linking, the present invention provides two methods for preparing the chlorine-resistant polyethylene pipe. The first method comprises the following steps:
[0042] (1) mixing polyvinyl alcohol, water and graphite uniformly, grinding them in a grinding wheel kettle, standing them to remove the precipitate after grinding, and obtaining an aqueous dispersion of polyvinyl alcohol edge-grafted modified graphene;
[0043] (2) adding a cross-linking agent and an optional catalyst to the aqueous dispersion to obtain a modified graphene dispersion;
[0044] (3) coating the modified graphene dispersion on the inner wall of a polyethylene pipe and drying the pipe to obtain the chlorine-resistant polyethylene pipe.
[0045] The second method includes the following steps:
[0046] (1) mixing polyvinyl alcohol, water and graphite uniformly, grinding them in a grinding wheel kettle, standing them to remove the precipitate after grinding, and obtaining an aqueous dispersion of polyvinyl alcohol edge-grafted modified graphene;
[0047] (2) coating the aqueous dispersion of the polyvinyl alcohol edge-grafted modified graphene on the inner wall of a polyethylene pipe, and performing physical crosslinking or radiation crosslinking and drying to obtain the chlorine-resistant polyethylene pipe.
[0048] The modified graphene material can be coated on the inside of the polyethylene pipe by any processing method such as spraying or scraping. In order to make the modified graphene material be better coated on the inner wall of the polyethylene pipe, the inner wall can be subjected to hydrophilic treatment such as corona treatment to increase the hydrophilicity of the inner wall. Since the PVA aqueous solution is viscous, it can be coated on the inner wall without hydrophilic treatment.
[0049] The coating process can be completed in steps after the polyethylene pipe is extruded, or it can be completed online during the polyethylene pipe extrusion process.
[0050] The present invention isolates the corrosion of the pipe by chloride ions by coating the polyethylene pipe with a coating containing graphene, thereby improving the service life of the pipe. The graphene coating used is prepared by graphite, PVA and water dispersion in a grinding disc, and the graphene is peeled off and PVA is grafted on the graphene through the action of the grinding disc, so that the graphene is evenly distributed and plays an isolating role.
[0051] The present invention will be further described below in conjunction with embodiments, but the scope of the present invention is not limited to these embodiments.
[0052] The test methods and characterization methods used in the following Examples 1-4 and Comparative Example 1 are as follows:
[0053] Test method for graphene exfoliation yield:
[0054] The mass of graphite material added to the grinding disc equipment is recorded as m1. After the suspension processed by the grinding disc is introduced into a container such as a beaker and left to stand for 10 hours, the unpeeled graphite material is precipitated at the bottom of the container, and the upper clear liquid is filtered using a vacuum filtration device. The bottom precipitate is washed and filtered 3-5 times in a cycle, and then the increased weight of the filter paper after filtering the bottom precipitate is dried and recorded as m2, which is the mass of the graphite material that has not been completely peeled.
[0055] Graphene exfoliation yield = (m1-m2) / m1
[0056] Characterization of graphene edge-grafted PVA:
[0057] Take 10 mL of the prepared graphene composition solution and add it to 200 mL of deionized water to dilute it evenly, then use a microporous filter membrane with a pore size of 0.22 microns to filter under reduced pressure, and finally use 2 L of deionized water to filter out free PVA. After drying, the purified PVA edge-grafted graphene is obtained for infrared characterization.
[0058] Characterization of size and thickness of graphene materials:
[0059] Take 10mL of the prepared graphene composition solution and add it to 200mL of deionized water for uniform dilution, then use a microporous filter membrane with a pore size of 0.22 microns to filter under reduced pressure, and finally use 2L of deionized water to filter out free PVA, and after drying, obtain the purified PVA edge-grafted graphene, which is evenly spread on the surface of a silicon wafer or a conductive adhesive, and observed by scanning electron microscopy to analyze the size of the graphene material. The purified graphene material is dispersed in ethanol, and after ultrasonication for 30 seconds, a small amount of dispersed liquid is dropped on the surface of a copper mesh for transmission electron microscopy observation, and the number of graphene material layers is obtained by analyzing the number of edges of the spread graphene material.
[0060] Determination of the mass content of the grafted PVA part in edge-grafted modified graphene:
[0061] The mass content of the grafted PVA portion in the edge-grafted modified graphene is measured by thermogravimetric analysis. Under the conditions of a sample nitrogen flow rate of 20.0 ml / min and a balance nitrogen flow rate of 40.0 ml / min, the mass loss of the PVA edge-grafted modified graphene sample is measured from 50.00°C to 800.00°C at a heating rate of 20.00°C / min, which is the mass content of PVA grafted to the graphene.
[0062] Preparation of graphene compositions
[0063] Example 1
[0064] 100.0 g of polyvinyl alcohol PVA (Sinopec Group Sichuan Vinylon Plant, brand 1799, degree of polymerization 1700) was dissolved in 1000 mL of deionized water, and then 150 g of 100 mesh flake graphite (Qingdao Santong Graphite Co., Ltd.) was added and stirred evenly. The grinding disc speed was set to 100 rpm. After 72 hours of circulation grinding, the graphene suspension processed by the grinding disc was poured into a beaker. After standing for 10 hours, the precipitate was filtered to obtain a stable aqueous dispersion of PVA grafted graphene, in which the mass fraction of grafted graphene was 4.5%. The graphene exfoliation yield was about 30%.
[0065] 10 mL of PVA-grafted graphene aqueous dispersion was added to 200 mL of deionized water for dilution, and then filtered under reduced pressure using a microporous filter membrane with a pore size of 0.22 μm. Finally, 2 L of deionized water was used to filter out free PVA, and purified PVA-grafted graphene was obtained after drying.
[0066] Figure 1 This is a scanning electron microscope photograph of the prepared PVA grafted graphene, the average size of its flakes is about 2.3 microns.
[0067] Figure 2 Transmission electron micrograph of the prepared PVA edge-grafted graphene.
[0068] Figure 3 The infrared spectrum of the prepared PVA edge-grafted graphene is shown in Figure 1. The infrared characteristic absorption peak of the PVA-grafted graphene is consistent with that of PVA. The infrared spectrum shows that at the wave number 3288cm -1 The characteristic absorption peak is the stretching vibration of -OH bonds between grafted PVA molecules or within the molecules in an associated form, with a wave number of 2935 cm -1 and 2904cm -1 The characteristic absorption peak is the asymmetric stretching vibration of -CH3 and -CH2- bonds, with a wave number of 1093 cm -1 The characteristic absorption peak is the hydroxyl characteristic absorption peak caused by -CO- stretching vibration, with a wave number of 1142cm -1 The characteristic absorption peak of is the characteristic absorption peak of hydroxyl group caused by -CC- stretching vibration. This indicates that PVA is grafted onto graphene. However, the infrared spectrum of flake graphite shows neither characteristic absorption peak of PVA nor characteristic peaks of other active functional groups. This indicates that the surface of flake graphite does not contain functional groups that can react with PVA. During the disc peeling process, the graphite flakes are broken, and there are many highly active carbon radicals on the edges of the newly generated graphite, which react with PVA in the solution to finally obtain PVA edge-grafted graphene.
[0069] Figure 4 The thermogravimetric analysis curves of pure flake graphite, PVA edge-grafted graphene and pure PVA. At 630°C, pure PVA loses nearly 100% of its weight, indicating that PVA has been almost completely decomposed into gas; flake graphite has almost no weight loss; PVA edge-grafted graphene loses 14% of its weight at this temperature, indicating that the mass content of grafted PVA in PVA grafted graphene is 14%.
[0070] Example 2
[0071] 50 grams of polyvinyl alcohol PVA (Sichuan Vinylon Factory, brand 1788) were dissolved in 1000 mL of deionized water, and 150 grams of 100 mesh flake graphite were added and stirred evenly. The grinding disc speed was set to 100 rpm. After 100 hours of circulation grinding, the graphite suspension processed by the grinding disc was poured into a beaker. After standing for 10 hours, the precipitation was filtered to obtain a stable aqueous dispersion of PVA edge-grafted graphene. The average size of the prepared graphene sheets was about 1.6-2.2 microns. The graphene stripping yield was about 37%. The mass content of graphene in the grafted graphene was 22%, and the mass content of PVA was 78%.
[0072] Example 3
[0073] 200 grams of polyvinyl alcohol PVA (Japanese Kuraray, brand CP1000) were dissolved in 1000mL deionized water, and 100 grams of 150 mesh flake graphite were added and stirred evenly. The grinding disc speed was set to 150rpm. After 100 hours of circulation grinding, the graphite suspension processed by the grinding disc was poured into a beaker. After standing for 10 hours, the precipitation was filtered to obtain a stable aqueous dispersion of PVA edge-grafted graphene. The number of graphene layers prepared was about 3-5 layers, and the size of the lamella was about 1 micron. The graphene stripping yield was about 31%. The content of graphene in the grafted graphene was 6%, and the content of PVA was 94%.
[0074] Example 4
[0075] 100 grams of polyvinyl alcohol PVA (Japanese Kuraray, brand CP1000) was dissolved in 1000mL deionized water, and then 100 grams of 100 mesh flake graphite was added and stirred evenly. The grinding disc speed was set to 75rpm. After 120 hours of circulation grinding, the graphite suspension processed by the grinding disc was poured into a beaker. After standing for 10 hours, the precipitation was filtered to obtain a stable aqueous dispersion of PVA edge-grafted graphene. The number of graphene layers prepared was about 6-10 layers, and the sheet size was about 1 micron. The graphene peeling yield was about 40%. The content of graphene in the grafted graphene was 10%, and the content of PVA was 90%.
[0076] Comparative Example 1
[0077] In 1000mL of deionized water, add 150g of 100-mesh flake graphite and stir evenly. Set the grinding wheel speed to 100rpm, circulate and grind for 100 hours, then pour the graphite suspension processed by the grinding wheel into a beaker and let it stand for 1 hour, and filter to remove the precipitate. The prepared graphene has a thickness of less than 5 layers and a flake size of less than 1 micron. The graphene exfoliation yield is about 3%.
[0078] Coating of the inner wall of polyethylene pipe
[0079] PVA gel content test:
[0080] Take 1-2g of the coating layer on the inner wall of the coated and cross-linked polyethylene pipe, put it in an oven at 90°C and fully dry it for 30 minutes, then weigh it and record it as m3. Put the dried sample in 1000mL water at 95°C for 1 hour and stir it thoroughly. Take it out after one hour and put it in an oven to dry at 90°C for 2 hours, then weigh it and record it as m4. The graphene content in the sample is recorded as X.
[0081] Then gel content = (m4-X) / (m3-X).
[0082] In the following Examples 5-8 and Comparative Examples 2-3, the polyethylene pipe used has an outer diameter of 10 cm, an inner diameter of 9.5 cm, and a length of 20 cm.
[0083] Example 5
[0084] Take 100g of the grafted graphene dispersion in Example 1, wherein PVA is about 8.73g, add 0.873g of glutaraldehyde as a cross-linking agent, and add 5g of HCl as a catalyst (Chinese medicine reagent, concentration 36%). Use a rolling brush to evenly apply the dispersion to the inner wall of a polyethylene pipe, then place the pipe in a 60°C baking oven for 1 hour, and the coating thickness is 1mm after drying. After the pipe is taken out, seal one end of the pipe first, then pour a chlorine-containing aqueous solution into the pipe, the chlorine concentration of which is 15mg / L, and finally seal the other end. After the pipe is soaked for 4 weeks, the seal is opened, and the treated pipe is cut to remove the inner wall coating layer and the oxidation induction period of the polyethylene material is tested according to the national standard GB / T 19466.6-2009, and the testing instrument is the DSC8000 produced by the American PE company, and the testing temperature is 200°C. The elongation test of the treated pipe was carried out in accordance with GB / T 8804.3-2003, and the testing instrument was the universal testing machine CMT4204 of Shenzhen Xinsansi Material Testing Company. The chlorine aging damage test of the sample was carried out in accordance with ASTM F2263-14 standard. Under the same conditions, the polyethylene pipes of the embodiment and the comparative example were exposed to pressurized circulating chlorinated drinking water, and the time of pipe rupture failure was recorded. The test temperature was 90°C, which was used to evaluate the long-term strength and toughness of the material in a chlorinated water environment. The testing instrument was an IPT chlorine resistance tester. The test results are shown in Table 1.
[0085] Comparative Example 2
[0086] Take a polyethylene pipe, seal one end of the pipe, then pour a chlorine-containing aqueous solution into the pipe, the chlorine concentration of which is 15 mg / L, and finally seal the other end. After the pipe is soaked for 4 weeks, the seal is opened, and the treated pipe is tested for the oxidation induction period of polyethylene materials according to the national standard "GB / T 19466.6-2009". The testing instrument is DSC8000 produced by the American PE company, and the testing temperature is 200°C. The elongation test of the treated pipe is carried out according to GB / T 8804.3-2003, and the testing instrument is the universal testing machine CMT4204 of Shenzhen Xinsansi Material Testing Company. The sample chlorine aging damage test is carried out according to ASTM F2263-14 standard. Under the same conditions, the polyethylene pipes of the embodiment and the comparative example are exposed to pressurized circulating chlorinated drinking water, and the time of pipeline rupture failure is recorded. The test temperature is 90°C, which is used to evaluate the long-term strength and toughness of the material in a chlorinated water environment. The testing instrument is an IPT chlorine resistance tester. The test results are shown in Table 1.
[0087] Comparative Example 3
[0088] Take 100g PVA aqueous solution (PVA is Sichuan Wei 1799, and the amount of PVA in the aqueous solution is 8.73g), add 0.873g glutaraldehyde as a cross-linking agent, and add 5g HCl as a catalyst (Chinese medicine reagent, concentration 36%). Use a rolling brush to evenly apply PVA to the inner wall of the polyethylene pipe, then place the pipe in a 60°C oven for 1 hour, and the coating thickness after drying is 1mm. After the pipe is taken out, one end is sealed first, and then a chlorine-containing aqueous solution is poured into the pipe, and its chlorine concentration is 15mg / L, and the other end is finally sealed. After the pipe is soaked for 4 weeks, the seal is opened, and the treated pipe is cut to remove the inner wall coating layer and the oxidation induction period of the polyethylene material is tested according to the national standard "GB / T19466.6-2009". The testing instrument is DSC8000 produced by the American PE company, and the test temperature is 200°C. The elongation test of the treated pipe was carried out in accordance with GB / T 8804.3-2003, and the testing instrument was the universal testing machine CMT4204 of Shenzhen Xinsansi Material Testing Company. The chlorine aging damage test of the sample was carried out in accordance with ASTM F2263-14 standard. Under the same conditions, the polyethylene pipes of the embodiment and the comparative example were exposed to pressurized circulating chlorinated drinking water, and the time of pipe rupture failure was recorded. The test temperature was 90°C, which was used to evaluate the long-term strength and toughness of the material in a chlorinated water environment. The testing instrument was an IPT chlorine resistance tester. The test results are shown in Table 1.
[0089] Example 6
[0090] Take 100g of the graphene composition dispersion in Example 2, wherein PVA is about 4.52g, and 2.26g of boric acid (Chinese medicine, purity greater than 99.8%) is added as a cross-linking agent. The dispersion is evenly coated on the inner wall of polyethylene pipe using the method of spraying, and then the pipe is placed in 80°C baking oven for 1 hour, and the coating thickness is 0.2mm after drying. After the pipe is taken out, one end is first sealed, and then a chlorine-containing aqueous solution is poured into the pipe, and its chlorine concentration is 15mg / L, and the other end is finally sealed. The pipe is opened and sealed after soaking for 4 weeks, and the treated pipe is cut and removed from the inner wall coating layer according to the national standard "GB / T19466.6-2009" to test the oxidation induction period of polyethylene material, and the testing instrument is the DSC8000 produced by the American PE company, and the test temperature is 200°C. The elongation at break test of the treated pipe was conducted in accordance with GB / T8804.3-2003, and the testing instrument was the universal testing machine CMT4204 of Shenzhen Xinsansi Material Testing Company. The chlorine aging damage test of the sample was conducted in accordance with ASTM F2263-14 standard. Under the same conditions, the polyethylene pipes of the embodiment and the comparative example were exposed to pressurized circulating chlorinated drinking water, and the time of pipe rupture failure was recorded. The test temperature was 90°C, which was used to evaluate the long-term strength and toughness of the material in a chlorinated water environment. The testing instrument was an IPT chlorine resistance testing machine. The test results are shown in Table 1.
[0091] Example 7
[0092] Take 100g of the graphene composition dispersion in Example 3, wherein PVA is about 16.2g, add 6.48g of epichlorohydrin (Chinese medicine, purity greater than 99.8%) as a cross-linking agent, add 3g of sodium hydroxide (Chinese medicine, analytically pure) as a catalyst to provide an alkaline environment. Use the method of spraying to evenly coat the dispersion on the inner wall of polyethylene pipe, then place the pipe in a 55°C baking oven for 10 hours, and the coating thickness is 0.4mm after drying. After the pipe is taken out, one end is first sealed, and then a chlorine-containing aqueous solution is poured into the pipe, and its chlorine concentration is 15mg / L, and the other end is finally sealed. After the pipe is soaked for 4 weeks, the seal is opened, and the treated pipe is cut and removed from the inner wall coating layer, and the oxidation induction period of polyethylene material is tested according to the national standard GB / T19466.6-2009, and the testing instrument is the DSC8000 produced by the American PE company, and the test temperature is 200°C. The elongation at break test of the treated pipe was conducted in accordance with GB / T8804.3-2003, and the testing instrument was the universal testing machine CMT4204 of Shenzhen Xinsansi Material Testing Company. The chlorine aging damage test of the sample was conducted in accordance with ASTM F2263-14 standard. Under the same conditions, the polyethylene pipes of the embodiment and the comparative example were exposed to pressurized circulating chlorinated drinking water, and the time of pipe rupture failure was recorded. The test temperature was 90°C, which was used to evaluate the long-term strength and toughness of the material in a chlorinated water environment. The testing instrument was an IPT chlorine resistance testing machine. The test results are shown in Table 1.
[0093] Example 8
[0094] Take 100g of the graphene composition dispersion in Example 4, wherein PVA is about 8.78g, add 1.75g of oxalic acid (Chinese medicine, purity greater than 99.8%) as a cross-linking agent, and add 3g of sodium hydroxide (Chinese medicine, analytically pure) as a catalyst to provide an alkaline environment. Use the method of the casting method to evenly coat the dispersion on the inner wall of the polyethylene pipe, then place the pipe at room temperature for 24 hours, and the coating thickness after drying is 0.4mm. After the pipe is taken out, one end is sealed first, and then a chlorine-containing aqueous solution is poured into the pipe, and its chlorine concentration is 15mg / L, and the other end is finally sealed. After the pipe is soaked for 4 weeks, the seal is opened, and the treated pipe is cut to remove the inner wall coating layer and the oxidation induction period of the polyethylene material is tested according to the national standard "GB / T 19466.6-2009". The testing instrument is DSC8000 produced by the American PE company, and the testing temperature is 200°C. The elongation at break test of the treated pipe was conducted in accordance with GB / T8804.3-2003, and the testing instrument was the universal testing machine CMT4204 of Shenzhen Xinsansi Material Testing Company. The chlorine aging damage test of the sample was conducted in accordance with ASTM F2263-14 standard. Under the same conditions, the polyethylene pipes of the embodiment and the comparative example were exposed to pressurized circulating chlorinated drinking water, and the time of pipe rupture failure was recorded. The test temperature was 90°C, which was used to evaluate the long-term strength and toughness of the material in a chlorinated water environment. The testing instrument was an IPT chlorine resistance testing machine. The test results are shown in Table 1.
[0095] Table 1 Gel content and oxidation induction period test results
[0096]
[0097]
[0098] It can be seen from the data in Table 1 that the polyethylene pipe with the edge-modified graphene coating on the inner wall has a significantly longer oxidation induction period, and its long-term strength and toughness in a chlorine-containing water environment are also significantly better than the pipe treated with a simple PVA aqueous solution and the untreated pipe. This shows that the composite material of PVA and graphene prepared by the present invention as the inner coating of the pipe can have a good barrier effect, thereby greatly improving the chlorine resistance of the polyethylene pipe.
[0099] The embodiments of the present invention have been described above, and the above description is exemplary, not exhaustive, and is not limited to the disclosed embodiments. Many modifications and changes will be apparent to those skilled in the art without departing from the scope and spirit of the described embodiments.
[0100] The endpoints and any values of the ranges disclosed in this article are not limited to the precise ranges or values, and these ranges or values should be understood to include values close to these ranges or values. For numerical ranges, the endpoint values of each range, the endpoint values of each range and the individual point values, and the individual point values can be combined with each other to obtain one or more new numerical ranges, which should be considered as specifically disclosed in this article.
Claims
1. A chlorine-resistant polyethylene pipe, characterized in that: The chlorine-resistant polyethylene pipe comprises a polyethylene resin layer as an outer layer and a modified graphene coating as an inner layer, wherein the modified graphene coating is a polyvinyl alcohol edge-grafted modified graphene coating, and at least part of the polyvinyl alcohol forms a cross-linked polyvinyl alcohol; Taking the total mass of the modified graphene coating as 100%, the mass content of polyvinyl alcohol in the modified graphene coating is 3-30%, preferably 5-25%, and the mass content of graphene is 70-97%, preferably 75-95%.
2. The chlorine-resistant polyethylene pipe according to claim 1, wherein: The oxidation induction period of the chlorine-resistant polyethylene pipe after being immersed in a chlorine-containing aqueous solution is greater than 25 minutes; the concentration of the chlorine-containing aqueous solution is 10-100 mg / L, and the immersion time is more than 3 weeks.
3. The chlorine-resistant polyethylene pipe according to claim 1, wherein: The thickness of the modified graphene coating is 0.1-2 mm.
4. The chlorine-resistant polyethylene pipe according to claim 1, wherein: Based on the total weight of the polyvinyl alcohol in the modified graphene coating being 100%, the gel content of the modified graphene coating is 60-100%, preferably 65-95%.
5. The chlorine-resistant polyethylene pipe according to claim 1, wherein: The modified graphene coating is formed by drying the modified graphene dispersion coated on the inner wall of the polyethylene resin layer; the modified graphene dispersion comprises an aqueous dispersion of polyvinyl alcohol edge-grafted modified graphene and a crosslinking agent.
6. The chlorine-resistant polyethylene pipe according to claim 5, wherein: The aqueous dispersion of polyvinyl alcohol edge-grafted modified graphene is obtained by exfoliating graphite through a grinding disc, and the exfoliation rate is 20-50%, preferably 25-40%.
7. The chlorine-resistant polyethylene pipe according to claim 5, wherein: The aqueous dispersion of polyvinyl alcohol edge-grafted modified graphene is prepared by a preparation method comprising the following steps: The polyvinyl alcohol, water and graphite are uniformly mixed and ground in a grinding wheel kettle. After the grinding, the mixture is allowed to stand and the precipitate is removed to obtain the aqueous dispersion of the polyvinyl alcohol edge-grafted modified graphene.
8. The chlorine-resistant polyethylene pipe according to claim 7, wherein: The graphite is natural graphite and / or artificial graphite, the natural graphite is selected from one or more of flake graphite, block graphite, and cryptocrystalline graphite, the artificial graphite is selected from one or more of thermal cracking graphite and highly oriented thermal cracking graphite, and the graphite is preferably flake graphite; the particle size of the graphite is 5-8000 mesh, preferably 35-3000 mesh, further preferably 50-1600 mesh, and more preferably 50-300 mesh.
9. The chlorine-resistant polyethylene pipe according to claim 7, wherein: The grinding is carried out in an open or closed system, preferably in a cyclic grinding at room temperature and normal pressure; the grinding conditions include: a rotation speed of 10-300 rpm, preferably 50-200 rpm; a time of 5-200 hours, preferably 10-150 hours, and more preferably 30-120 hours.
10. The chlorine-resistant polyethylene pipe according to claim 7, wherein: Taking the total mass of polyvinyl alcohol and water as 100%, the mass fraction of the polyvinyl alcohol is 2-40%, preferably 3-30%, and more preferably 5-20%.
11. The chlorine-resistant polyethylene pipe according to claim 7, wherein: The average sheet diameter of the polyvinyl alcohol edge-grafted modified graphene is 1-5 μm.
12. The chlorine-resistant polyethylene pipe according to claim 5, wherein: The cross-linking agent is at least one of aldehydes, acids, propylene oxide, and heavy metal salts, preferably at least one of glutaraldehyde, boric acid, and oxalic acid; Based on the total mass of polyvinyl alcohol contained in the aqueous dispersion of polyvinyl alcohol edge-grafted modified graphene as 100%, the added amount of the cross-linking agent is 10-50%, preferably 10-35%.
13. The chlorine-resistant polyethylene pipe according to claim 1, wherein: The modified graphene coating is formed by physically crosslinking or radiation crosslinking and drying an aqueous dispersion of polyvinyl alcohol edge-grafted modified graphene coated on the inner wall of a polyethylene resin layer.
14. The chlorine-resistant polyethylene pipe according to claim 13, wherein: The radiation crosslinking uses at least one of gamma rays, electron beams, X-rays and ultraviolet light.
15. The method for preparing the chlorine-resistant polyethylene pipe according to any one of claims 1 to 12, comprising the following steps: (1) mixing polyvinyl alcohol, water and graphite uniformly, grinding them in a grinding wheel kettle, standing them to remove the precipitate after grinding, and obtaining an aqueous dispersion of polyvinyl alcohol edge-grafted modified graphene; (2) adding a cross-linking agent and an optional catalyst to the aqueous dispersion to obtain a modified graphene dispersion; (3) coating the modified graphene dispersion on the inner wall of a polyethylene pipe and drying the pipe to obtain the chlorine-resistant polyethylene pipe.
16. The method for preparing the chlorine-resistant polyethylene pipe according to any one of claims 13 to 14, comprising the following steps: (1) mixing polyvinyl alcohol, water and graphite uniformly, grinding them in a grinding wheel kettle, standing them to remove the precipitate after grinding, and obtaining an aqueous dispersion of polyvinyl alcohol edge-grafted modified graphene; (2) coating the aqueous dispersion of the polyvinyl alcohol edge-grafted modified graphene on the inner wall of a polyethylene pipe, and performing physical crosslinking or radiation crosslinking and drying to obtain the chlorine-resistant polyethylene pipe.
17. The method according to claim 15 or 16, wherein: The coating method is scraping or spraying; The inner wall of the polyethylene pipe is optionally subjected to a corona treatment prior to the coating step.
18. The method according to claim 17, wherein: The coating is completed in a step after the polyethylene pipe is extruded, or is completed online during the polyethylene pipe extrusion process.
Citation Information
Patent Citations
Graphene composite metal film and preparation method thereof
CN106374111A
Modified polyvinylalcohol graphene, preparation method and application thereof
CN107673336A
Preparation method of graphene oxide / polyvinyl alcohol composite coating
CN109608674A
Preparation method of highly dispersed graphene
CN110577757A
Graphene / water-soluble polymer composite material and preparation method thereof
CN111925697A
Cited By
Multi-layer composite pipe as well as preparation method and application thereof
CN120137241A